THE SPIRITUAL INTELLIGENCE IN INTERPRETING THE RELIGIOUS DAYS COMMEMORATION BY CROSS-RELIGIOUS OF MALAY SOCIETY IN THE EDUCATIONAL INSTITUTION - Muslimah Muslimah (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
This study aims to describe the form of the religious day celebrations of Malay society across religions and the meaning of commemorating them in educational institutions. This field research uses a qualitative research approach with data collection through in-depth interviews, participant level observation and documentation. The results of the study describe that the form of religious day commemoration activities in SMPN 2 Arut Selatan are grouped into two, namely: commemoration of religious days which are commemorated based on certain moments, for instance are maulid of the Prophet Muhammad, Isra Mi'raj, and celebrations to welcome the Islamic New Year (Islam), Christmas and Easter (Christian Protestant and Catholic); and routine religious activities, for example is prayer with each of the followers of interfaith religions. Furthermore, the meanings of the religious days celebration are grouped into three views, trere are; as the obligation/ necessity of the learning process, empirical religion and individual's religion; as a culture / habit that becomes a system at school; as a requirement for the implementation of religious practices; and as a culture related to the commemoration of religious days.